Energy Supply for the Chemoautotroph Ferrobacillus ferrooxidans - Dugan, Patrick R. (1965)
Dugan, Patrick R. (Syracuse University, Syracuse, N.Y.), and Donald G. Lundgren. Energy supply for the chemoautotroph Ferrobacillus ferrooxidans. J. Bacteriol. 89:825–834. 1965.—A working model is proposed to explain dissimilatory ferrous iron oxidation by Ferrobacillus ferrooxidans, that is, oxidation linked to an energy source. The model is supported by experimental evidence reported here as well as in the literature. Polarographic assays of the culture medium demonstrated an iron “complex” involving oxygen. The initial “complex” would be oxygenated, but not oxidized because no electron transport has taken place. The “complex” is formed in solution or on the cell surface and is somehow reacted with iron oxidase (or oxygenase), resulting in the release of an electron. Either sulfate or a flavoprotein is suggested as involved in the initial electron-transfer link between iron and the cell. The electron is transported in the cell through a typical electron-transport system involving coenzyme Q(6), cytochrome c, and cytochrome a; oxygen is the final electron acceptor. Electron micrographs of intact and sectioned cells are included to show structural detail in support of the model.